Strategy in Teaching Writing To The Tenth Graders of Vocational High School: A Case Study - Aditama Melati Melati; Nunung Suryati; Enny Irawati (Universitas Lancang Kuning, 2023)
Abstract: This study aimed to describe vocational high school teacher’s strategy in teaching writing. There are difficulties faced by the students in writing English text such as grammar, vocabularies, sentence structure, stating the idea, etc. In this case, the researcher wanted to see how the strategy chosen by the teacher could minimize the students problem in writing. This study emplys descriptive qualitative research that describes the findings and discusssion mostly inwords rather than number. This study was conducted in 10 RPL Evercoss class. The instruments used are field notes, observation sheet, students’ questionnaire consists of seven questions, and teacher’s interview guide, and questionnaire. It was found that the students of 10 RPL Evercoss class were enjoying the activity in their teaching and learning process prepared by the teacher. They found moving table enjoyable and fun to learn how to write English text. In addition, the students feel more motivated to learn how to write in English better using the moving table.